The European Union in Global Security - Ginsberg, R. author. aut Link
XXVI, 270 p.
Keywords: Does the EU matter in international security? The authors identify and explain the drivers of and brakes to EU foreign security action, offer methods of assessment to ascertain influence, and conclude that the union has become a niche international security provider that has in turn strengthened EU foreign policy.